1985
DOI: 10.1523/jneurosci.05-01-00215.1985
|View full text |Cite
|
Sign up to set email alerts
|

Conditioned modification of phototactic behavior in Hermissenda. II. Differential adaptation of B-photoreceptors

Abstract: Changes in the response of B-type photoreceptors to illumination were examined in the isolated nervous systems of Hermissenda following the conditioning procedures described in the preceding paper. Analysis of the transient peak amplitude of the depolarizing generator potential at the onset of two of the three light intensities used in the behavioral studies did not reveal an enhanced photoresponse to the light. However, when the activity of the same B-photoreceptors was examined after 5 min of continuous ligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
48
1

Year Published

1987
1987
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 10 publications
5
48
1
Order By: Relevance
“…The ratio is expressed as A/(A ϩ B), where A represents pretraining scores and B represents post-training scores. Conditioned animals exhibited behavioral suppression that was similar in magnitude to previous reports (Crow and Alkon, 1978;Crow and Offenbach, 1983;Crow, 1985). After postaquisition testing, all animals were coded so that the collection of electrophysiological data was conducted using blind experimental procedures.…”
Section: Methodsmentioning
confidence: 54%
See 2 more Smart Citations
“…The ratio is expressed as A/(A ϩ B), where A represents pretraining scores and B represents post-training scores. Conditioned animals exhibited behavioral suppression that was similar in magnitude to previous reports (Crow and Alkon, 1978;Crow and Offenbach, 1983;Crow, 1985). After postaquisition testing, all animals were coded so that the collection of electrophysiological data was conducted using blind experimental procedures.…”
Section: Methodsmentioning
confidence: 54%
“…The details of the conditioning procedures and methods for testing phototactic behavior have been described previously in detail (Crow and Alkon, 1978;Crow and Offenbach, 1983;Crow, 1985) and will be described only briefly in this report. Animals were tested before training to determine baseline latencies to initiate locomotion in response to a test light.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies of associative learning in Hermissenda have shown that pavlovian conditioning results in long-term intrinsic enhanced excitability of neurons in the CS pathway (Crow and Alkon, 1980;Farley and Alkon, 1982;West et al, 1982;Crow, 1985;. Voltage-clamp studies identified a reduction in several K ϩ currents, I A and I K,Ca , as contributors to conditioning-dependent enhanced excitability (Alkon et al, Ϫ1 , where V 1/2 is the half-activation voltage, and k m is the maximum slope.…”
Section: Discussionmentioning
confidence: 99%
“…In Hermissenda, one site of intrinsic excitability changes produced by pavlovian conditioning is neurons in the conditioned stimulus (CS) pathway (Crow and Alkon, 1980;Farley and Alkon, 1982;Alkon et al, 1985;Crow, 1985Crow, , 1988Goh et al, 1985;Matzel et al, 1990;Frysztak and Crow, 1993, 1997Gandhi and Matzel, 2000;. In animals that exhibit intrinsic enhanced excitability, a cytoskeletal-related protein, the phosphorylation of which is regulated by conditioning, has been identified in components of the CS pathway Xue-Bian, 2000, 2002).…”
Section: Introductionmentioning
confidence: 99%